Programmable composite pipeline structure supporting scheduling of integrated network and computing - HOU Saifeng; CUI Pengshuai; HU Yuxiang; DONG Yongji; LIU Yi (Tongxin xuebao)
To meet the needs of differentiated QoS assurance and efficient heterogeneous resources scheduling of diversified services in the ICN environment, for the performance bottleneck faced by traditional network architecture, a programmable composite pipeline architecture that supported ICN resource scheduling and QoS guarantee was designed. The network function pipeline deployment system supported the QoS isolation guarantee of different network functions and the allocation of heterogeneous resources in the programmable composite pipeline architecture. The scheduling algorithm was dynamically adjusted based on the hierarchical scheduling mechanism of programmable queuing to adapt to the characteristic service QoS guarantee requirements. The heterogeneous resource allocation strategy was solved based on resource pricing and cooperative game to realize the flexible scheduling of computing and network resources in the process of data forwarding. Experiment results demonstrate that the proposed method can effectively isolate the performance interference, meet the customized QoS requirements of diversified services, and reduce the system overhead caused by heterogeneous resource competition.